E-services adoption processes by firms in developing nations - Quaddus, M. A.; Woodside, Arch G. (Emerald, 2015)
This volume serves to recognize the uniqueness of the moment; the number of new users of e-services worldwide will double during 2015-2018 (moving from 2 billion users mostly living in the developed nations to an additional 2 billion users mostly living in developing nations). This radical embrace of new e-service technologies will substantially improve the quality of lives for most residents globally. A profound happening occurring now! The new technologies combine rapidly delivering of a multitude of services at extremely low cost to adopters now having extremely low incomes relative to residents living in developed nations. Adoption of e-service among residents in developing nations ends the debate as to whether or not marketing to the bottom of the pyramid is possible. The more relevant issues focus on describing and explaining e-service adoption processes in developing nations. How are these processes being implemented? What obstacles had to be overcome in achieving these adoptions? How were these obstacles overcome? Read this volume for research providing useful answers to these questions.
Keywords: Computer networks -- Developing countries.; Information technology -- Developing countries.; elektronické knihy; electronic books